Biodiversity of Mangrove Vegetation in Rivers, Estuaries and Coastal Areas in Saronggi Subdistrict, Sumenep - Ferdiansyah, Akhmad; Ali, Mahrus (Electronic Journal of Education, Social Economics and Technology, 2024)
Mangrove vegetation is the vegetation that makes up coastal ecosystems which are the largest ecosystems in Indonesia that provide ecosystem functions and services to marine-terrestrial biota and surrounding communities. Mangrove vegetation is a transitional ecosystem that is directly influenced by land and sea so that transitional areas such as river mouths and coasts. Rivers, estuaries and sea coasts are important components in optimizing the growth and development of mangroves. It is necessary to calculate the biodiversity of mangrove vegetation in rivers, estuaries and coasts in Saronggi District. The aim is to know the types and levels of mangrove vegetation biodiversity as well as studying the effect of environmental parameters on mangrove vegetation biodiversity in rivers, estuaries and coasts Saronggi District, Sumenep Regency. The method used is the quadratic transect combined with Stratified Random Sampling. The results of the mangrove diversity index value by dividing the area were obtained: the diversity index value in the coastal area was 1.379187 in the low category, the estuary area was 3.048782 in the high category, and the river area was 2.863279 in the medium category. The species diversity index in Saronggi District yielded 3.206173 in the high category. This indicates that Saronggi District has a high diversity of mangrove species/vegetation. Several factors became the basis for the existence of a high diversity index due to the large number of species found in Saronggi District, namely a total of 38 mangrove species with details of 22 true mangrove species and 16 associated mangrove species, dominated by Sonneratia alba, Rhizophora mucronata, Sonneratia caseolaris, Rizhophora stylosa and Nypa fruticans, with the highest important value index is Sonneratia alba with a value of 53.38%, Rhizophora mucronata (24,924%) and Nypa fruticans (20,71%).